Chronic immune sensorimotor polyradiculopathy: Report of a case series. Issue 6 (25th February 2019) - Thammongkolchai, Thananan; Suhaib, Omer; Termsarasab, Pichet; Li, Yuebing; Katirji, Bashar
ABSTRACT: Introduction: Chronic immune sensorimotor polyradiculopathy (CISMP) is a chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) variant affecting both sensory and motor nerve roots without evidence of peripheral nerve demyelination. Methods: We report a case series of 9 patients with CISMP, identified from 2 tertiary centers. Clinical, electrodiagnostic, and neuroradiologic features, and treatment responses, were retrospectively reviewed. Results: Patients presented with sensorimotor deficits and hypo‐/areflexia, predominantly involving lower extremities. Three had cranial nerve involvement. Electrodiagnostic findings in all patients localized to roots proximal to dorsal root ganglia, without evidence of peripheral nerve demyelination. Cerebrospinal fluid examination revealed an albuminocytologic association. Eight patients exhibited gadolinium enhancement and thickening of multiple spinal nerve roots and/or cranial nerves. All patients demonstrated good responses to immunotherapies. Discussion: CISMP is similar to CIDP in many aspects, but lacks typical electrodiagnostic findings of peripheral nerve demyelination. It is important to recognize this unusual and treatable entity. Muscle Nerve 59:658–664, 2019 Abstract : See editorial on pages 640–642 in this issue .